Low carbon car taxation and its potential to accelerate transitions to a low carbon transport sector in the UK - Brand, C; Tran, M; Anable, J (European Council for an Energy Efficient Economy (eceee), 2011)
The transition to a low carbon transport world requires a host of demand and supply policies to be developed and deployed. Pricing and taxation plays a major role, as it affects purchasing behaviour, overall ownership and use of vehicles. This paper explores the energy and environmental effects of a number of key car pricing and taxation instruments, including graded purchase taxes, vehicle excise duties and vehicle scrappage incentives. It employs the UK Transport Carbon Model to develop long term scenarios of low carbon fiscal policies and their effects on transport demand, vehicle stock evolution, life cycle energy use and carbon emissions in the UK. The analysis addresses the central question: which type of taxation on low carbon cars accelerates fuel, technology and purchasing behavioural transitions the fastest with (i) most life cycle emissions savings, (ii) most revenue generation for the treasury and (iii) suppressed car use. The results suggest that policy choice, design and timing can play crucial roles in meeting multiple policy goals. Both CO2 grading and tightening of CO2 limits over time are crucial in achieving the transition to low carbon mobility. The car purchase ‘feebate’ policies are most effective in accelerating low carbon technology uptake and reducing cumulative life cycle GHG emissions by between 165 to 524 MtCO2 eq by 2050. Designed carefully they can avoid overburdening consumers with ever more taxation, which creates a political acceptance problem in the case of graduated VED. However, VED schemes can provide handy revenue streams to governments that could be recycled in accompanying low carbon measures. Scrappage schemes are found to save little carbon and may even increase emissions on a life cycle basis. The main policy implication of this work is that in order to achieve a transition to low carbon transport system governments should focus on designing incentive schemes with strong up-front price signals that reward ‘low carbon’ and penalise ‘high carbon’,